Über das vollständige Objekt eines Strahlenkomplexes im mehrdimensionalen projektiven Raum - Grincevičius, K. (Lithuanian Mathematical Journal, 1962)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: К. И. Гринцевичюс, О полном объекте комплекса прямых в многомерном проективном пространстве K. Grincevičius, Apie tiesių komplekso pilną objektą daugiamatėje projektyvinėje erdvėje